2019
DOI: 10.29252/hehp.7.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health Promoting Lifestyle Behaviors in Hospital Staff of Guilan University of Medical Sciences

Abstract: The effect of health promoting intervention on healthy lifestyle and social support in elders ... [2] Lifestyle of university students in Kashan, Iran and factors ... [3] A global view on the development of non communicable ... [4] The effect of education based on BASNEF model on ... [5] The impact of educational intervention to increase self efficacy and awareness ... [6] Iranian nursing staff's self-reported general and mental health related to working ... [7] The educational program based on the successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…These results had a higher mean HPLP II score than the Turkish study among nurses [21]. Similar results regarding BMI were found in a study conducted at Iran's Guilan University of Medical Sciences [22]. According to a study on healthy habits among Saudi university students, 31.3% of participants had a body mass index (BMI) above the healthy range.…”
Section: Discussionsupporting
confidence: 75%
“…These results had a higher mean HPLP II score than the Turkish study among nurses [21]. Similar results regarding BMI were found in a study conducted at Iran's Guilan University of Medical Sciences [22]. According to a study on healthy habits among Saudi university students, 31.3% of participants had a body mass index (BMI) above the healthy range.…”
Section: Discussionsupporting
confidence: 75%
“…Our results may be due to the majority of nurses working in this hospital being seniors and having an awareness of their own health responsibilities. Like Estebsari et al (2019), this finding found a significant correlation between BMI, Health Responsibilities, and Nutritional habits. Contrary to the study by Kurnat-Thoma et al (2017), health responsibility is the lowest, scoring HPLP-II (2.55), indicating the respondents did not always feel accountable for maintaining their well-being.…”
Section: Discussionsupporting
confidence: 54%
“…The World Health Organization (WHO) 2012 announced that lifestyle-related diseases account for 40-50% of fatalities in less developed nations and 70-80% in affluent nations. According to Estebsari et al (2019), a global assessment of health and quality of life (QOL) conducted by the World Health Organization (WHO) shows that 60% of QOL is lifestyle-dependent. The term "lifestyle" refers to the conditions and manner of human existence.…”
Section: Introductionmentioning
confidence: 99%